Impact forces upon landing single, double, and triple revolution jumps in figure skaters - Lockwood, K.; Gervais, P. (Clinical Biomechanics, 1997)
INTRODUCTION: Competitive success in the sport of figure skating has been largely attributed to the skater's ability to execute multi-revolution jumps, landing backwards, on a single leg, in a prescribed configuration. The extent to which additional revolutions contributes to greater vertical force upon landing was assessed to determine if advanced technical feats places these young athletes at risk of potential impact related injuries. METHODS:: Twenty four competitive figure skaters ranging in technical classification (Juvenile, Novice, and Senior) and age (10 to 26 yrs.) respectively, gave their informed consent to participate in the study. Skaters were asked to execute single, double, and triple revolution jumps to the best of their ability. Landing impact data between the plantar surface of the foot and the insole of the skate was quantified with the use of the Micro EMED Insole System (Novel GmbH, Munich, Germany). The insole was placed inside the skate of the landing foot, tethered to the leg with the data acquisition unit secured to the lower back of the subject. In addition, all trials were video taped by four Panasonic cameras. Three dimensional video analyses were later performed using the Ariel Performance Analysis System and used to co-ordinate the impact data with the technical aspects of the jumps. The EMED Extern -- Multimask Software Package was employed to process the Micro EMED data. The foot was divided into two regions for data analysis: rearfoot (0-50% of the length of the pressure print) and forefoot (50-100% of the length of the pressure print). Impact forces and foot pressure data were then analysed and the results documented for the following variables: Peak impact force (%BW), Peak pressure (N/cm(2)), Pressure time integral (Impulse-N/cm(2)), Force time integral (Impact-%BW) and measures of the Peak force-time differences between the fore and rearfoot (ms). A repeated measures analysis of variance was performed to determine significant differences among the above listed variables, between jumps and between groups as stipulated by their technical classifications (p = 0.05). RESULTS:: ANOVA results indicated that gender differences were not significant for any of the examined variables, thus gender groups were collapsed for further analysis. Statistically significant differences in peak impact force (%BW) and time sequencing of foot contacts (ms) were revealed both between jumps and groups (p < 0.05). An analysis of effect size examined the magnitude of the differences in impact force and force-time differences of triple revolution jumps. A range of moderate (0.5) to large (1.3) differences in relative force and force-time differences between single, double, and triple jumps and technical classifications were detected. Furthermore, an inverse relationship was found between relative force (N/kg) and time differences between the fore and rearfoot peak force contacts (m/s). DISCUSSION:: The relationship between relative impact force and time delay between fore and rearfoot contacts suggests that the time taken to distribute the force of triple revolution jumps is significantly less than the singles and doubles. Although jump height was not quantified as a primary purpose of this investigation, subsequent kinematic analyses revealed that jump height was not significantly different among single, double, and triple revolution jumps. Therefore, increased height is not suggested as possible cause of higher impact force or shorter footfall time. However, it is suggested that the increased time required for rotation places the skater closer to the ice at time of impact. A 'collision type' landing seems to be a result of higher revolution jumps. Decreasing the time to properly dissipate the force may also suggest that the impact propagated through the lower extremity musculo-skeletal system is of greater magnitude and intensity introducing greater potential for injury.